2013
DOI: 10.1111/bij.12123
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific molecular phylogeny and phylogeography of theMeriones meridianus(Rodentia: Cricetidae) complex in northern China reflect the processes of desertification and the Tianshan Mountains uplift

Abstract: The phylogeographical patterns and demographic history of mitochondrial DNA (cytochrome b, N = 327; D-loop, N = 252) and nuclear DNA (IRBP gene, N = 235) haplotypes were studied for the Meriones meridianus complex in northern China, a desert-dwelling gerbil species complex. The phylogenetic analyses, which were performed on the separate and combined (mitochondrial + nuclear) datasets, revealed two divergent clades (Clade A and Clade B) corresponding to distinct geographical regions. Clade A contained the haplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 84 publications
3
34
1
Order By: Relevance
“…Furthermore, G. nanus DNA sequences do show strong genetic structure patterns (Bray et al., ; Ndiaye et al., ). Furthermore, two recent studies conducted on the gerbil genus Meriones have both shown genetic structure patterns associated with physical barriers (Dianat, Darvish, Cornette, Aliabadian, & Nicolas, ; Wang, Zhao, Fang, Liao, & Liu, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, G. nanus DNA sequences do show strong genetic structure patterns (Bray et al., ; Ndiaye et al., ). Furthermore, two recent studies conducted on the gerbil genus Meriones have both shown genetic structure patterns associated with physical barriers (Dianat, Darvish, Cornette, Aliabadian, & Nicolas, ; Wang, Zhao, Fang, Liao, & Liu, ).…”
Section: Discussionmentioning
confidence: 99%
“…The GTR model was run for the entire population and for each D-loop haplogroup separately. Substitution rate for the D-loop sequences estimated for Meriones was similar to Microtus [84]. We used the substitution rate of 1.27 × 10 −7 substitutions per site per year in D-loop estimated for Meriones meridianus (95% confidence interval = 1.2 × 10 −7 to 1.33 × 10 −7 /site/year) [84] to scale the time axis of BSPs.…”
Section: Methodsmentioning
confidence: 99%
“…Substitution rate for the D-loop sequences estimated for Meriones was similar to Microtus [84]. We used the substitution rate of 1.27 × 10 −7 substitutions per site per year in D-loop estimated for Meriones meridianus (95% confidence interval = 1.2 × 10 −7 to 1.33 × 10 −7 /site/year) [84] to scale the time axis of BSPs. The chains were run for 200 (entire samples) and 40 (haplogroups) million iterations respectively, of which the first 10% were discarded.…”
Section: Methodsmentioning
confidence: 99%
“…Keeping this in mind, the comparison of obtained genetic divergence between lineages with previously published studies can nonetheless give interesting clues. The Cytb genetic distance among species of the genus Meriones ranges from 12.3% to 20.5% (Wang, Zhao, Fang, Liao, & Liu, ). Between subspecies, it is 1.4% in Meriones tamariscinus (Bray et al, ), it ranges from 6.7% to 7.5% in M. meridianus (Bray et al, ) and it ranges from 2.5% to 9.6% in M. persicus (Dianat et al, ).…”
Section: Discussionmentioning
confidence: 99%